A novel multi-objective hybrid QoS optimisation technique for MANETs. (2018) - Jayavenkatesan, Rangaraj; Mariappan, Anitha
Mobile ad hoc network (MANET) requires the support of optimisation techniques for improving the quality of service (QoS) it delivers. Optimisation becomes mandatory due to the autonomous and infrastructure less characteristics of the network. This manuscript formulates a hybrid optimisation by assimilating ant colony optimisation (ACO) and fitness distance ratio (FDR)-based particle swarm optimisation (PSO) to improve the performance of the network. For ensuring better QoS, ACO is aimed at optimal solution based on throughput maximisation. Contrarily, the FDR PSO considers overhead and residual energy for précising the optimal solution further. The proposed hybrid technique is implemented in a scenario consisting of 100 mobile nodes and the performance of the proposed technique is investigated using the metrics throughput, packet delivery ratio, delay, overhead and energy.